2009
DOI: 10.1161/circulationaha.108.817528
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus Activates Signal Transduction Pathways Resulting in Vascular Endothelial Growth Factor Resistance of Human Monocytes

Abstract: Background-Monocytes are cellular components of wound repair, arteriogenesis, and atherogenesis. Vascular endothelial growth factor (VEGF)-A and placental growth factor recruit monocytes to sites of arteriogenesis via stimulation of VEGF receptor-1 (VEGFR-1). The chemotactic response of monocytes to VEGF-A is attenuated in individuals with diabetes mellitus (DM). This VEGF resistance correlates with impaired collateral growth. The aim of this study is to elucidate the molecular basis of VEGF resistance and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 43 publications
(36 reference statements)
7
94
0
5
Order By: Relevance
“…Inflammatory cells have been shown to accumulate in the ischemic area and positively modulate neovascularization and arteriogenesis through various mechanisms, including production of angiogenic factors, secretion of proinflammatory cytokines, and matrix degradation (Arras et al, 1998;Tamarat et al, 2002;Silvestre et al, 2003;Stabile et al, 2003Stabile et al, , 2006Hong et al, 2005;Waeckel et al, 2005Waeckel et al, , 2006Hillmeister et al, 2011). In diabetes, monocyte dysfunction and reduced VEGF production have been observed (Waltenberger et al, 2000;Tchaikovski et al, 2009;Waltenberger, 2009;Carr et al, 2011). Consistent with these studies, we observed a sharp reduction in number of infiltrated macrophages and decreased VEGF protein level in ischemic muscles of diabetic mice compared with nondiabetic mice.…”
Section: Discussionsupporting
confidence: 88%
“…Inflammatory cells have been shown to accumulate in the ischemic area and positively modulate neovascularization and arteriogenesis through various mechanisms, including production of angiogenic factors, secretion of proinflammatory cytokines, and matrix degradation (Arras et al, 1998;Tamarat et al, 2002;Silvestre et al, 2003;Stabile et al, 2003Stabile et al, , 2006Hong et al, 2005;Waeckel et al, 2005Waeckel et al, , 2006Hillmeister et al, 2011). In diabetes, monocyte dysfunction and reduced VEGF production have been observed (Waltenberger et al, 2000;Tchaikovski et al, 2009;Waltenberger, 2009;Carr et al, 2011). Consistent with these studies, we observed a sharp reduction in number of infiltrated macrophages and decreased VEGF protein level in ischemic muscles of diabetic mice compared with nondiabetic mice.…”
Section: Discussionsupporting
confidence: 88%
“…Diabetic individuals show delayed reepithelialisation [106] and altered sensitivity to VEGF resulting in decreased angiogenesis [107].…”
Section: Pathologies/comorbiditiesmentioning
confidence: 99%
“…3-5 These trends have also been observed in cases of acute myocardial infarction (MI), and DM is associated with rehospitalization for heart failure 6 after PCI. These differences have been reported to be due to chronic hyperglycemia, because it induces vascular endothelial injury, 7 inflammatory reactions, 8 reactive oxygen species or advanced glycation end products, which leads to accelerated cell proliferation 9 or other pathological conditions such as in the blood-clotting system or fibrinolysis. 10 Thus, we have to overcome such problems in DM patients undergoing PCI, although the rate of stent restenosis has decreased since the introduction of drug-eluting stents (DES).…”
mentioning
confidence: 99%